INDIA'S IT EXPORT BOOM: CHALLENGES AHEAD - Joseph, KJ and Harilal, KN (Centre for Development Studies-WP317, 2001)
Given the manifold ways, in which the information technology could contribute to human welfare, the developing countries have invested in Information Technology (IT) as a short cut to prosperity. India too has not been left much behind in this bandwagon and series of initiatives were made by the government to promote the IT sector in India. These efforts seem to have paid rich dividend in terms of IT sector emerging as one of the vibrant components in India's export basket. Moreover India has been able to establish credibility in the international IT markets. Given the boom in the world market for software the firms in software industry could afford to pay wage rate much higher than that offered by other sectors. Of late, the developed countries have come forward to relax the visa restrictions to Indian software personnel. This in turn is expected to facilitate the free movement of skilled manpower from India. In the light of these developments in India's IT sector the present paper seeks answers to three crucial questions. First, how to characterize India's recent performance in software exports? Secondly, what are the implications of boom in the IT export sector on other sectors competing for the skilled manpower? Thirdly, are there any threats to the sustained growth of India's software exports? To answer the first question, we critically analyze the recent trends in India's software exports in terms of its structure and growth and highlights some of the disquieting aspects of India's IT export boom. To answer the second and third questions we develop a model drawing insights from the specific factors model. With the help of the model the paper highlights some of the emerging challenges which were generally overlooked in the existing literature. It was observed that the phenomenal increase in the export growth notwithstanding, the net export earning might be only in the range of 50 per cent. The study underlined the need for a structural transformation of the India's IT export sector through enhancing its value addition capability so as to achieve the target of $50 million exports by the year 2008. It is also argued that the boom in the software export sector is likely to adversely affect the growth prospects of other sectors, which compete for skilled manpower in the short run. This is primarily on account of the resource movement effect associated with IT export boom. This in turn could have adverse effect on the growth prospects of IT sector itself in the long run. Finally it is shown that the move towards relaxation in the visa restriction for Indian software manpower initiated by the developed economies is likely to pose a major threat for the sustained growth and competitiveness of India's IT exports.